يعقوب المنصور الموحدي اسهاماته العلمية وعلاقته بالعلماء (580-595ه - 1184-1199م) - دقة، القدري, عوادي، لزهر (جامعة الوادي University of eloued, 2018)
لقد شهدت الدولة الموحدية في عهد يعقوب المنصور الموحدي، أوج عطائها وإزدهارها وهذا ما عكسته شخصية المنصور في ذلك من خلال إكتسابه للخبرة السياسية خلال فترة ولاية عهده في الأندلس وإقباله الكبير على شتى العلوم ومشاركته في الجهاد ضد النصارى إلى جانب أبيه أبي يعقوب يوسف بن عبد المؤمن، بالإضافة إلى مساهمته الفعالة في تشجيع مختلف الفئات في المجتمع الموحدي والدفع بعجلة النمو والتطور الفكري، وتشجيعه للعلوم والفنون وخاصة منها العلوم الدينية والشرعية لأهميتها والتي كان هو أول وأبرز السباقين إلى الإخذ بها وتقريب العديد من الفلاسفة والأطباء وفطاحلة العلماء والبلغاء، حتى صار مجلسه مضربا للأمثال من خلال المناظرات والحلق التي تعقد فيه، وتشجيع المنصور لها، ومنها كانت تبرز ملامح علاقة المنصور بالعلماء حيث أهتم بالمتصوفة وقربهم إليه وبالغ في إجلالهم وتعظيمهم، وكذلك الحال بالنسبة للفلاسفة خاصة منهم إبن رشد الذي كان من أقرب المقربين له، إلا أنه كان صارما وحازما مع أتباع المذهب المالكي وطريقة تعامله مع الفقه المالكي وعلمائه، وعمل على الحد من إنتشاره في مقابل تشجيع المذهب الظاهري والتعظيم من شأنه كونه المذهب الرسمي للدولة. " " The Almohad state, under the reign of Jacob Al-Mansur al-Muhadi, witnessed the peak of its prosperity and prosperity. This was reflected by the personality of Al-Mansour in that through his acquisition of political experience during the period of his reign in Andalusia and his great interest in various sciences and his participation in Jihad against the Christians. , In addition to its effective contribution to the promotion of various groups in the monotheistic society and to accelerate the growth and development of intellectual, and encourage the science and the arts, especially religious sciences and legitimacy of its importance, which was the first and most prominent races to take and bring together many philosophers and doctors, Al-Mansour, who was a prominent figure in Al-Mansur's relationship with the scholars, was interested in the Sufism, near them, and in their reverence and magnanimity, as well as for the philosophers, especially Ibn Rushd, who was one of the closest confidants. To him, but he was firm and firm with the followers of the Maliki school and the manner of dealing with the Maliki jurisprudence and scientists, and worked to reduce the spread in exchange for the promotion of the doctrine of virtualization and maximization would be the official doctrine of the state.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي الوسيط والمعاصر
Keywords: الاسهامات العلمية-العلماء - التطور الفكري.; Scientific contributions- Scientists-Intellectual development; Scientific contributions- Scientists-Intellectual development